Clinical impact of induction treatment modalities and optimal timing of radiotherapy for the treatment of limited-stage NK/T cell lymphoma. (October 2016) - Moon, Joon-Ho; Lee, Bo-Hee; Kim, Jeong-A; Lee, Yoo Jin; Chae, Yee Soo; Yhim, Ho-Young; Kwak, Jae-Yong; Do, Young Rok; Park, Yong; Song, Moo-Kon; Shin, Ho-Jin; Kim, Therasa; et al.
Highlights: Radiotherapy was the most important factor for achieving CR with limited stage ENKTL. An increased risk of systemic relapse during radiotherapy with CCRT. Frontline ASCT remains a therapeutic option for patients with high-risk features. Abstract: This study retrospectively investigated the optimal timing of radiotherapy (RT) in patients with limited-stage extranodal NK/T-cell lymphoma (ENTKL). Among 158 patients with newly diagnosed stage I/II ENKTL, 61 patients were treated with sequential chemotherapy followed by radiotherapy (SCRT), 55 with concurrent chemoradiotherapy followed by non-anthracycline-based chemotherapy (CCRT/CT), and 42 with chemotherapy (CT) only. The 5-year overall survival (OS) rate did not differ between SCRT (77.7 ± 5.5%) and CCRT/CT (68.9 ± 6.8%; p = 0.234). In the SCRT group, 18 patients (29.5%) relapsed within the RT field and 6 (9.8%) at systemic sites, while in the CCRT/CT group, 9 patients (16.4%) relapsed at the primary site and 14 (25.5%) at systemic sites. The 5-year cumulative incidence of relapse (CIR) at primary sites was 26.3% and 19.2% after SCRT and CCRT/CT (p = 0.308), while the 5-year CIR of systemic sites was 8.7% and 26.5% after SCRT and CCRT/CT, respectively (p = 0.010). In the multivariate analysis, NK/T-cell Prognostic Index score and CR achievement were the most important prognostic factors for survival. Although up-front RT had limitations in systemic disease control and was associated with an increased risk of systemic relapse during RT compared to SCRT, timing of RT did not significantly affect survival outcomes.